2023
DOI: 10.1007/s00018-023-04921-6
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 transactivates the FOSL1 gene through STAT3 and enhances glioma stemness

Shanchun Guo,
Vanajothi Ramar,
Alyssa A. Guo
et al.

Abstract: Introduction We previously reported that TRPM7 regulates glioma cells’ stemness through STAT3. In addition, we demonstrated that FOSL1 is a response gene for TRPM7, and the FOSL1 gene serves as an oncogene to promote glioma proliferation and invasion. Methods In the present study, we determined the effects of FOSL1 on glioma stem cell (GSC) markers CD133 and ALDH1 by flow cytometry, and the maintenance of stem cell activity by extreme limiting dilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…To further gain insight into the mechanism by which TRPM7 activates transcription of the FOSL1 gene to contribute to glioma stemness, we constructed a FOSL1 promoter and its GAS mutants followed by luciferase reporter assays and ChIP-qPCR. These combined results demonstrated that TRPM7 induced FOSL1 transcriptional activation, which is mediated by the action of STAT3, a mechanism shown to be important in glioma stemness [16].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…To further gain insight into the mechanism by which TRPM7 activates transcription of the FOSL1 gene to contribute to glioma stemness, we constructed a FOSL1 promoter and its GAS mutants followed by luciferase reporter assays and ChIP-qPCR. These combined results demonstrated that TRPM7 induced FOSL1 transcriptional activation, which is mediated by the action of STAT3, a mechanism shown to be important in glioma stemness [16].…”
Section: Introductionmentioning
confidence: 71%
“…This modification results in the cancer cells acquiring stemness properties, which represents a critical step in the development and progression of cancer [41]. Our most recent studies demonstrated that deacetylation of FOSL1 at the Lys-16 residue located within its DNA binding domain leads to an increase in FOSL1 transcriptional activity [16].…”
Section: Post-translational Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The collective findings indicate that TRPM7 triggers the activation of FOSL1 transcription, which is facilitated by the activity of STAT3. This process has been identified as crucial in maintaining the stemness of glioma cells [21].…”
Section: Regulation Of Fosl1 21 Transcriptional Regulationmentioning
confidence: 99%